PENGARUH MODEL DISCOVERY LEARNING TERHADAP KREATIVITAS SISWA PADA PEMBELAJARAN SENI MUSIK DI KELAS VII SMP - Delta, Juliana; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The background of the researchwas the lack of year VII students’ creativity in music and arts subject. This was because almost all of the materials in the subject given in form of lecture and conventional. This also caused the students were less trained in developing their creativity in music works. The aim of this research was to find out the influence of discovery learning model on students’ creativity in music and arts subject of year VII students of State Junior High School 1 Sungai Betung Bengkayang Regency.The approach used in this research was quantitative and the method used was true experiment. The design used waspretest-posttest control group design. The sample were students of VII A as many as 32 pupils as experimental classandstudents of VII B as many as 32 pupils as control class. The data collecting technique used were direct observation and measurement technique, whereasthe data analysis techniques used were descriptive and statistical analysis with median and t-test. Based on the analysis result of the influence of discovery learning model on students’ creativity in music and arts subject of year VII students of State Junior High School 1 Sungai Betung Bengkayang Regency by comparing experimental and control class, it showed tcountgained were 7,288 whereas ttablegained were 1.999 with 5% of level of singnificance for two sides and degree of freedom of 62. Because the value of tcount ˃ ttable, then null hypothesis was rejected. It meant there was influence of discovery learning on students’ creativity in music and arts subject of year VII students of State Junior High School 1 Sungai Betung Bengkayang Regency. In conclusion, discovery learning model has significant influence on students’ creativity.Key Words: Discovery Model Learning, Students’ Creativity.